Neonatal septicemia: Its etiological agents and clinical associates - Verma, Pramila; Sadawarte, Kalpana (Indian Journal of Child Health, 2015)
Aim: To identify the common bacterial pathogens associated with neonatal sepsis and to study their systemic, focal, and hematological associates. Design: Retrospective hospital-based observational study. Setting: Level II neonatal intensive care unit. Subjects: Totally, 87 neonates with culture proven sepsis. Materials and Methods: Case records of admitted neonates (from January 2013 to December 2013) with culture-positive sepsis were reviewed. Data were collected in a predesigned proforma and analyzed for type of bacterial isolate, and clinical and hematological manifestations of sepsis. Results: Blood culture was positive in 36.8% (87/236) of the neonates with sepsis. Among the culture-positive cases, 58.62% (51/87) were male, and 51.72% (45/87) were preterm babies. Staphylococcus aureus was the most commonly isolated organism (51, 58.62% cases), followed by Klebsiella in 14 (16.09%), coagulase-negative Staphylococcus in 6 (6.89%), Acinetobacter species in 4 (4.59%), Escherichia coli in 4 (4.59%), Citrobacter freundii in 2 (2.29%), Pseudomonas aeruginosa in 2 (2.29%), and Candida species in 2 (2.29%) babies. Conclusions: S. aureus was the predominant pathogenic organism in both inborn and outborn babies while Klebsiella was the main culprit for causing sepsis in outborn babies.